Urgensitas Masyarakat Madani Civil Society dalam Mengurai Problematika Sosial: Suatu Tinjauan Terhadap Varian Konflik di Lombok - Ihsan Hamid (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2019)
Civil society movement post Reformation gained momentum, it is marked by a growing number of emerging elements of civil society itself with various forms of movement and activities performed. The dynamics of this at once indicates that the process of Westernization of the nation of Indonesia, because of the progress of the process therein, of course, involve the participation of the public good in giving control of the Government as well as the active participation in the effort of maintaining the harmony node civic social dam in an attempt tomecegah the conflict and remained consistent in providing solutions to the issues facing the nation. On that basis then the existence of a civil society necessary existence. For it was at least the civil society movementcan be manifested into some kind of social movements. The first symbolic resistance, which includes various indirect actions to control the domination of the country. Secondly, pragmatic resistance that wasconducted as a direct reaction against the wisdom of the Government or the system of socio-economic-political progress, including in this case be a solution for all social problems. Third, the symbolic resistance-which isa pragmatic action directly or indirectly to the creation of socio-political situation that demands better especially young wong and also demanded a reduction in State control against the various areas of life the community.